The Role of External Stakeholders in the Development of Innovations by IT Companies in Lubuskie Voivodeship - Monika INKÓW (Communications of International Proceedings, 2022)
The analysis of literature on management reveals that the number of publications on competitive advantage has been systematically increasing for many years. These publications deal with various aspects of competitive advantage, including its sources. An organization’s innovativeness is often identified as one of the sources of competitive advantage because it is innovation that allows the enterprise to achieve better results than its competitors do. Therefore, it is extremely important to identify the determinants of innovation and assess their impact on enterprises’ innovativeness. One of the factors that can be treated as initiating innovation in an enterprise is the external and internal stakeholders of the organization. The aim of this study is to determine the role of external stakeholders in undertaking and developing innovations by companies from the IT industry in Lubuskie Voivodeship. In order to achieve the above-mentioned research goal, the author conducted research among the owners and representatives of the management staff of companies from the IT industry in Lubuskie Voivodeship.
Keywords: innovation; stakeholders; IT sector